Method for preparing nano lanthanum hexaboride through lanthanum chloride hydrate assisted microwave solid-phase combustion
Through the hydrated lanthanum chloride-assisted microwave solid-phase combustion method, solid-phase combustion reaction was carried out under microwave conditions, which successfully solved the problems of long time and high temperature and high pressure in the preparation of nano lanthanum hexaboride, and achieved efficient preparation of uniform and fine nano lanthanum hexaboride powder.
Patent Information
- Application Number
- CN202510305136.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The prior art has problems such as long time, high temperature and high pressure, requiring atmosphere protection, difficult to control particle size at the nanoscale, and incomplete reaction of amorphous boron powder and difficult to remove.
The mixture was prepared by hydrated lanthanum chloride-assisted microwave solid-phase combustion method by molar ratio of hydrated lanthanum nitrate, amorphous boron powder, urea, ammonium nitrate and lanthanum chloride, and a solid-phase combustion reaction was carried out under microwave conditions. The microwave absorption characteristics of hydrated lanthanum chloride were used to promote the reaction and control the particle size.
It has achieved the preparation of uniform and fine nano-lanthanum hexaboride powder with uniform particles in a short time, solving the problem of residual amorphous boron powder, and synthesized in the air without reducing the atmosphere, and has the advantages of one-step phase formation, gentle and controllable reaction, controllable particle size, short time consumption and high yield.
Smart Images

Figure CN119797387A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano powder preparation, and in particular relates to a method for preparing nano lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride. Background Art
[0002] LaB6 was found to be a stable compound with a cubic structure. The stoichiometry is expressed as LaB6. The sample shows purple, while the boron-rich LaB9 shows blue. Due to the strong bonding of B atoms, LaB6 has low work function (2.4eV~2.6eV), high melting point (2715℃), high thermal stability, low volatility and high mechanical strength. Therefore, LaB6 can be used in aerospace, electronic information, 5G medical, environmental protection and other fields. Due to its unique properties, LaB6 particles have a local surface plasmon resonance effect in the near-infrared region, and have extremely strong light absorption properties in the near-infrared region with a wavelength of 750~1000 nm. This makes the material have higher light absorption properties at a lower addition amount, and is expected to be used in building / automotive glass insulation.
[0003] In recent years, people have proposed a variety of controlled synthesis methods for ultrafine / nano lanthanum hexaboride. Since lanthanum hexaboride is a superhard material, the solid-phase mechanochemical method requires long-term high-energy ball milling under high-temperature vacuum conditions, long reaction time, micron-level particles, and low purity; metal thermal reduction and boron carbide reduction methods need to be carried out under inert gas protection, have long reaction times, and uneven particles; NaBH4 as a boron source RAPET method and NaBH4-Mg reduction method need to be carried out under high pressure and have a relatively shortened time, but the reaction is difficult to control and prone to explosion; The plasma method for preparing LaB6 is simpler, but requires 30KW of energy, long reaction time, high energy consumption, and uneven particles.
[0004] A Chinese patent (publication number CN111285380A) discloses a method for preparing and using a multi-rare earth doped boride and its heat insulation powder. The method of the invention is to dry a rare earth source and a boron source containing two rare earth elements and mix them with an additive, ball mill them, and then subject the mixture to microwave treatment. The temperature used in this method is lower than that of other methods, and the temperature is 500~1000℃. However, the additives used in this method, such as magnesium powder, aluminum powder, iron powder, metallic sodium, and metallic potassium, are all active metal elements, which are very likely to generate electric sparks during microwave heating, causing combustion and explosion, and are extremely dangerous.
[0005] A Chinese patent (publication number CN114873601B) discloses a method for preparing ultrafine rare earth boride materials by low-temperature synthesis using microwave heating. The method of the invention is to ball-mill a monovalent rare earth chloride hydrate, a monovalent rare earth bromide hydrate and magnesium diboride together and then dry them, and then microwave them. This method requires a temperature of 100-180°C in the microwave. It needs to be carried out under vacuum conditions, and the reaction energy is all provided by microwaves. The microwave power is high and the time is long, and the energy consumption is extremely high. At the same time, the boron source is magnesium diboride, which will introduce metal impurities into the system, and magnesium diboride is difficult to remove.
[0006] Unique Preparation of Hexaboride Nanocubes: A First Example of BorideFormation by Combustion Synthesis[J]. J. Am. Ceram. Soc., 93
[10] 3136–3141(2010) proposed a method for solid phase combustion synthesis of rare earth lanthanum hexaboride. The method is to manually mix lanthanum nitrate, amorphous boron powder and carbohydrazide, heat and ignite them in a muffle furnace, and then wash and dry them to obtain lanthanum hexaboride. The method takes place in a short time and is relatively simple and convenient. However, the synthesis process of the method is violent, and the submicron-scale products obtained are uneven in size and severely agglomerated. In addition, amorphous boron powder remains in the product, which greatly affects the optical properties of lanthanum hexaboride. In addition, the fuel used in the method is carbohydrazide, which is expensive and toxic, and is not conducive to industrial application.
[0007] Chen Weifan's team previously studied the preparation of nano-lanthanum hexaboride by solution combustion and submitted a Chinese patent application (publication number CN 113666382 A). The relevant research paper (Peng Rong, Combustion synthesis and performance study of LaB6 nanopowder for thermal insulation glass [D]. Nanchang University, 2023) proposed a method for synthesizing rare earth lanthanum hexaboride by solution combustion / solution microwave combustion. The method is to mix lanthanum nitrate (La(NO3)3·6H2O) and amorphous micron boron powder (B), fuel carbohydrazide and glycine in an agate mortar, and then put them into a muffle furnace or microwave oven to ignite. After the combustion is completed, they are first washed by centrifugation with hydrochloric acid and deionized water, and finally dried to obtain the powder. The synthesis process of this method is intense, and the particle size is 100~200nm in the most ideal state. It can be clearly seen in the SEM image of nano-lanthanum hexaboride that the product synthesized by this method contains unreacted amorphous boron powder and other by-products, which greatly affects the optical properties and high-purity powder application. Summary of the invention
[0008] In view of the problems existing in the above-mentioned ultrafine / nano lanthanum hexaboride preparation method, such as long time, high temperature and high pressure, need for atmosphere protection, especially difficulty in controlling the particle size at the nanometer level, incomplete reaction when amorphous boron powder is used as the boron source, and difficulty in removing the remaining amorphous boron powder, the present invention proposes a method for preparing nano lanthanum hexaboride by hydrated lanthanum chloride assisted microwave solid-phase combustion.
[0009] The invention uses hydrated lanthanum nitrate as a lanthanum source and an oxidant, amorphous boron powder as a boron source, urea as a fuel, and ammonium nitrate as an additional oxidant. The addition of hydrated lanthanum chloride provides an excess of lanthanum source, promotes a complete reaction, and inhibits the agglomeration and sintering of the intermediate product nano-lanthanum oxide during the reaction. The specific process is as follows: since hydrated lanthanum chloride has the characteristic of strongly absorbing microwaves, it heats up rapidly under microwave irradiation, first removes part of the crystal water, and then forms lanthanum chloride oxide (LaCl3·7H2O=LaCl3+7H2O, LaCl3+2H2O=La(OH)2Cl+2HCl, La(OH)2Cl=LaOCl+H2O), in situ wrapping the surface of nano-lanthanum oxide formed by low-temperature combustion, preventing it from agglomerating and sintering. At about 800℃, lanthanum oxychloride can be completely converted into lanthanum oxide (2LaOCl+1 / 2O2=La2O3+Cl2↑), and finally uniform and fine particles of intermediate lanthanum oxide are obtained, which promotes the boron heat and boration reaction caused by combustion heat to be complete (La2O3+7B=LaB6+LaBO3), solving the problem of large particles and incomplete reaction of amorphous boron powder in previous combustion synthesis and difficult removal. (According to the literature: Yao Chao, Preparation of Nano-lanthanum Oxide [J]. Journal of Chemical Engineering of Colleges and Universities, (2003) 06-0685-04, the study shows that the thermal decomposition temperature of lanthanum chloride is low, and it will lose all crystal water and turn into lanthanum oxychloride at about 400-450℃). This method is synthesized under air without reducing atmosphere, and has the advantages of one-step phase formation, mild reaction, controllable particle size, short time consumption, high yield and simple equipment. The overall reaction equation is as follows: 2La(NO3)3·7H2O+5CH4N2O+7B=LaB6+LaBO3+22H2O↑+5CO2↑+8N2↑; 2LaCl3·7H2O+1 / 2O2+7B=LaB6+LaBO3+Cl2↑+4HCl+12H2O.
[0010] The present invention is achieved through the following technical solution: a method for preparing nano lanthanum hexaboride by hydrated lanthanum chloride assisted microwave solid phase combustion, comprising the following steps: S1. According to the molar ratio of 10:96:(50-75):1:6, respectively weigh hydrated lanthanum nitrate, amorphous boron powder, urea, ammonium nitrate and hydrated lanthanum chloride, mix them evenly to obtain a mixture; S2, placing the mixture into a microwave reactor, and performing a solid phase combustion reaction under microwave conditions; S3. Take out the solid phase combustion reaction product, wash it with acid and water, separate it and dry it to obtain nano lanthanum hexaboride.
[0011] Specifically, in step S2, the solid phase combustion reaction time is 1 to 10 minutes.
[0012] Specifically, in step S2, the microwave frequency of the microwave reactor is 915 MHz-2450 MHz.
[0013] Specifically, the acid used for pickling in step S3 is hydrochloric acid or sulfuric acid.
[0014] Specifically, the average particle size of the obtained nano lanthanum hexaboride is about 50 nm.
[0015] Compared with the existing preparation method of lanthanum hexaboride, the present invention has the beneficial effects of: using hydrated lanthanum nitrate as lanthanum source and oxidant, amorphous boron powder as boron source, urea as fuel, ammonium nitrate as additional oxidant, hydrated lanthanum chloride as reaction promoter and morphology controller and providing additional lanthanum source, successfully preparing nano lanthanum hexaboride powder with uniform particle dispersion in a very short time. The present invention introduces lanthanum chloride into the reactant to strongly absorb microwaves during solid-phase microwave combustion, promotes the complete reaction of amorphous boron powder and refines the product grains, and quickly converts it into nano lanthanum oxychloride to encapsulate the refined lanthanum oxide grains during the microwave combustion process. The additional lanthanum oxychloride is converted into lanthanum oxide in the subsequent combustion, and then undergoes efficient boronization reaction with boron to obtain uniform nano lanthanum hexaboride, solving the problem of residual amorphous boron powder in the product. The method is synthesized under air without reducing atmosphere, has the advantages of one-step phase formation, mild and controllable reaction, controllable particle size, short time consumption, high yield and simple equipment, and has broad prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 It is the X-ray diffraction pattern of the comparative example sample.
[0017] Figure 2 It is the scanning electron microscope image of the comparative sample.
[0018] Figure 3 This is the X-ray diffraction pattern of the sample in Example 1.
[0019] Figure 4 This is a scanning electron microscope image of the sample in Example 1. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the comparative examples and embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments.
[0021] A method for preparing nano-lanthanum hexaboride by hydrated lanthanum chloride assisted microwave solid phase combustion comprises the following steps: S1. According to the molar ratio of 10:96:(50-75):1:6, respectively weigh hydrated lanthanum nitrate, amorphous boron powder, urea, ammonium nitrate and hydrated lanthanum chloride, mix them evenly to obtain a mixture; S2, placing the mixture into a microwave reactor, and performing a solid phase combustion reaction under microwave conditions of a microwave frequency of 915 MHz to 2450 MHz for 1 to 10 minutes; S3, taking out the solid phase combustion reaction product, washing it with acid, washing it with water, separating it, and drying it, so as to obtain nano lanthanum hexaboride with an average particle size of about 50nm. The acid used for the acid washing is hydrochloric acid or sulfuric acid. Comparative Example
[0022] S1. Based on the preparation of 22 g of lanthanum hexaboride, 43.3 g of lanthanum nitrate hexahydrate, 6.49 g of amorphous boron powder, 4.5 g of urea and 0.8 g of ammonium nitrate were weighed respectively, and mixed evenly to obtain a mixture.
[0023] S2. The mixture was placed in a microwave reactor and reacted for 5 minutes under microwave conditions at a microwave frequency of 915 MHz.
[0024] S3. Take out the solid phase combustion reaction product, clean it with dilute hydrochloric acid and deionized water, centrifuge it and dry it to obtain a comparative example sample. Example 1
[0025] S1. Based on the preparation product amount of 35 g, accurately weigh 43.3 g of lanthanum nitrate hexahydrate, 10.4 g of amorphous boron powder, 4.5 g of urea, 0.8 g of ammonium nitrate and 22.3 g of lanthanum chloride heptahydrate, and mix them evenly to obtain a mixture.
[0026] S2. The mixture was placed in a microwave reactor and subjected to solid phase combustion reaction at a microwave frequency of 915 MHz for 5 minutes.
[0027] S3. Take out the solid phase combustion reaction product, clean it with dilute hydrochloric acid and deionized water, centrifuge it and dry it to obtain the sample of Example 1. Example 2
[0028] S1. Based on the preparation product amount of 35 g, accurately weigh 43.3 g of lanthanum nitrate hexahydrate, 10.4 g of amorphous boron powder, 7.5 g of urea, 0.8 g of ammonium nitrate and 22.3 g of lanthanum chloride heptahydrate, and mix them evenly to obtain a mixture.
[0029] S2. The mixture was placed in a microwave reactor and subjected to solid phase combustion reaction at a microwave frequency of 2450 MHz for 1 minute.
[0030] S3. Take out the solid phase combustion reaction product, clean it with dilute hydrochloric acid and deionized water, centrifuge it and dry it to obtain the sample of Example 2. Example 3
[0031] S1. Based on the preparation product amount of 35 g, accurately weigh 43.3 g of lanthanum nitrate hexahydrate, 10.4 g of amorphous boron powder, 7.5 g of urea, 0.8 g of ammonium nitrate and 22.3 g of lanthanum chloride heptahydrate, and mix them evenly to obtain a mixture.
[0032] S2. The mixture was placed in a microwave reactor and subjected to solid phase combustion reaction for 10 minutes under microwave conditions at a microwave frequency of 915 MHz.
[0033] S3. Take out the solid phase combustion reaction product, clean it with dilute sulfuric acid and deionized water, centrifuge it and dry it to obtain the sample of Example 3.
[0034] Figure 1 The X-ray diffraction pattern of the comparative sample is shown in FIG.
[0035] Figure 2 This is a scanning electron microscope photo of the comparative sample. As shown in the figure, the sample particles present an obvious cubic structure, the local surface is smooth, the particle size is 500~2000nm, and there is flocculent amorphous boron powder nearby, indicating that the amorphous boron powder in the comparative example has not reacted completely and there is residue.
[0036] Figure 3 and Figure 4 They are the X-ray diffraction pattern and scanning electron microscope image of the sample in Example 1. Figure 3 As shown in FIG. 1 , the characteristic diffraction peaks of the sample in Example 1 and the characteristic diffraction peaks of lanthanum hexaboride of PDF#73-1699 are significantly broadened compared with the comparative sample, indicating that the grain size is significantly reduced; Figure 4 As shown, the particles of the sample in Example 1 are uniform and spherical, with an average particle size of 50 nm, and no flocculent amorphous boron powder is found.
[0037] Table 1
[0038] As shown in Table 1, the atomic ratio of La to B in the comparative sample is 1:8.43 based on EDS spectrum analysis, which deviates from 1:6 of lanthanum hexaboride, indicating that the amorphous boron powder is not completely reacted and there is residue. The color of the sample is light brown, which can be seen from Figure 2 The presence of flocculent amorphous boron powder in the sample of Example 1 is confirmed. The atomic ratio of La to B in the sample of Example 1 is 1:5.99, which is very close to 1:6 of lanthanum hexaboride, indicating that the amorphous boron powder is almost completely reacted. Figure 4 The absence of flocculent amorphous boron powder was confirmed.
[0039] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the scope of the present invention.
Claims
1. A method for preparing nano-lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride, characterized in that: The steps include: S1. According to the molar ratio of 10:96:(50-75):1:6, respectively weigh hydrated lanthanum nitrate, amorphous boron powder, urea, ammonium nitrate and hydrated lanthanum chloride, mix them evenly to obtain a mixture; S2, placing the mixture into a microwave reactor, and performing a solid phase combustion reaction under microwave conditions; S3. Take out the solid phase combustion reaction product, wash it with acid and water, separate it and dry it to obtain nano lanthanum hexaboride.
2. The method for preparing nano-lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride according to claim 1, characterized in that: In step S2, the solid phase combustion reaction time is 1 to 10 minutes.
3. The method for preparing nano lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride according to claim 1, characterized in that: In step S2, the microwave frequency of the microwave reactor is 915 MHz-2450 MHz.
4. The method for preparing nano-lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride according to claim 1, characterized in that: The acid used for pickling in step S3 is hydrochloric acid or sulfuric acid.
5. The method for preparing nano-lanthanum hexaboride by microwave solid phase combustion assisted by hydrated lanthanum chloride according to claim 1, characterized in that: The average particle size of the obtained nano lanthanum hexaboride is 50 nm.
Citation Information
Patent Citations
Preparation method of nano rare earth hexaboride
CN113666382A
Preparation method of nano-rare earth boride materials by low-temperature synthesis using microwave heating
CN114873601B
Method for producing nanoparticulate lanthanoide / boron compounds or solid substance mixtures containing nanoparticulate lanthanoide / boron compounds
CN101198546A
Method for preparing nano superfine rare-earth hexaboride powder
CN101948117A
Preparation method of lanthanum hexaboride nanometer powder and application of lanthanum hexaboride nanometer powder
CN106395843A